(untitled) (Journal of Plant Disease Sciences, 2017)
Prunus necrotic ring spot virus (PNRSV) is one of the most devastating ilarviruses infecting ornamental flowers, stone and pome fruits. There are numerous reports of PNRSV infecting cherry, almond and rose from India and other parts of the world. Peach ( ) is one of the most important commercial stone Prunus persica fruits in mid hills of Himachal Pradesh. Plants were surveyed on the basis of visual symptoms such as necrotic rings and distortion of mid vein from different orchards of Shimla, Solan, Sirmour and Kullu districts to record the prevalence of PNRSV. Based on visual symptoms, the disease incidence was found to range between 1-18 percent. PNRSV being a latent virus, cannot be assessed by symptoms alone. Thus DAS-ELISA was used for quick and reliable method for confirming the presence of this virus in Peach plants.